2020
DOI: 10.1136/flgastro-2020-101521
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes to radiation safety and cholangiogram interpretation in endoscopic retrograde cholangiopancreatography (ERCP): a UK survey

Abstract: BackgroundFluoroscopy during endoscopic retrograde cholangiopancreatography (ERCP) exposes staff and patients to potentially harmful ionizing radiation. We performed a UK survey to explore trainee and trainer attitudes to radiation protection and cholangiogram interpretation in ERCP.MethodsAn electronic 10-point survey was prospectively distributed to endoscopy unit leads, training programme directors between October and November 2019. Only UK-based ERCP trainees and trainers with hands-on procedural exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Therefore, rigorous and continuous education in radiation safety is a mandatory aspect of ERCP training, focusing on parameters that minimize patient radiation exposure. The use of pulsed fluoroscopy, frame rate modification and collimation is strongly recommended to continuously reduce patient radiation exposure during ERCP procedures [22,23]. However, several studies have highlighted the lack of and the need for correct education in radiation protection during ERCP training [22,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, rigorous and continuous education in radiation safety is a mandatory aspect of ERCP training, focusing on parameters that minimize patient radiation exposure. The use of pulsed fluoroscopy, frame rate modification and collimation is strongly recommended to continuously reduce patient radiation exposure during ERCP procedures [22,23]. However, several studies have highlighted the lack of and the need for correct education in radiation protection during ERCP training [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…The use of pulsed fluoroscopy, frame rate modification and collimation is strongly recommended to continuously reduce patient radiation exposure during ERCP procedures [22,23]. However, several studies have highlighted the lack of and the need for correct education in radiation protection during ERCP training [22,23].…”
Section: Discussionmentioning
confidence: 99%
“… 22 , 23 Indeed, this does appear to be a concern for ERCP trainees; a recent survey study reported that only 26% of trainees received formal training and 97% expressed a desire for further training. 24 Therefore, maximizing operator cholangiogram interpretation is imperative to maximize the therapeutic efficacy of ERCP.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers collected the data online via Google Form, which was prepared in line with the literature (hong & Shin, 2014;Siau et al, 2021;Yun & park, 2020) and included questions related to the subject. The form consisted of 30 questions including descriptive characteristics of nurses and the effect of radiation on ERcp nurses.…”
Section: Data Collection Tool and Proceduresmentioning
confidence: 99%